Thermally conductive molded body

CN122935579APending Publication Date: 2026-10-16SEKISUI POLYMATECH CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202580020424.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-03-29
Filing Date
2025-03-28
Publication Date
2026-10-16

AI Technical Summary

Benefits of technology

[0039] According to the present invention, thermally conductive molded articles with excellent thermal conductivity and formability can be provided.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The heat conductive molded body of the present application is characterized by being a heat conductive molded body containing a polymer matrix and a heat conductive filler material, and the relationship between the gel fraction a (mass %) of the heat conductive molded body and the content b (volume %) of the polymer matrix satisfies both of the following formula (1) and formula (2). a > 1.25 x b - 4.1 Formula (1) a < 2.87 x b - 33 Formula (2) According to the present application, a heat conductive molded body excellent in heat conductivity and moldability can be provided.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to thermally conductive molded bodies. Background Technology

[0002] For electronic devices such as computers, automotive parts, and mobile phones, heat sinks or other heat dissipation components are generally used to dissipate heat generated by heat-generating elements such as semiconductor components and mechanical parts. It is known that thermally conductive materials such as thermally conductive sheets or grease are placed between the heat-generating element and the heat sink to improve the heat transfer efficiency.

[0003] While heat sinks and heat generators can also be made of materials with flat surfaces, the increasing complexity of device structures in recent years has led to a rise in materials with varying heights, irregularities, and other shapes. Therefore, thermally conductive materials are required to be three-dimensional shapes that can conform to the complex forms of heat sinks and heat generators.

[0004] Patent Document 1 discloses an invention relating to a three-dimensional thermally conductive molded body containing thermally conductive materials and silicone-based materials, and describes how, based on this three-dimensional thermally conductive molded body, sufficient gap filling and contact area can be ensured without applying excessive stress to heat dissipation components such as heat sinks.

[0005] Patent Document 2 discloses an invention relating to a thermally conductive retainer molded from a thermally conductive composition in which a thermally conductive filler material is mixed into a silicone rubber raw material, as a thermally conductive retainer that can impart excellent thermal conductivity and is easy to install. The aforementioned thermally conductive composition is characterized in that the thermally conductive filler material is contained in a proportion of 40 to 70% by volume relative to the total volume of the silicone rubber raw material and the thermally conductive filler material, and magnesium oxide with an average particle size of 5 μm or less is contained in a proportion of 35 to 100% by volume relative to the total volume of the aforementioned thermally conductive filler material, and the hardness (Type A hardness tester) of the cured thermally conductive composition is in the range of 20 to 70.

[0006] Existing technical documents

[0007] Patent documents

[0008] Patent Document 1: Japanese Patent No. 7053484

[0009] Patent Document 2: Japanese Patent Application Publication No. 2005-56837 Summary of the Invention

[0010] The problem that the invention aims to solve

[0011] Thermally conductive molded bodies with three-dimensional shapes need to have high thermal conductivity and excellent formability. That is, when thermally conductive molded bodies are molded using molds, etc., during the manufacturing process, sometimes the material is damaged or a part remains in the mold, and the desired three-dimensional shape cannot be obtained. Therefore, it is necessary to prevent this situation.

[0012] One method to impart excellent thermal conductivity is to increase the amount of thermally conductive filler material and to improve the gap filling and contact area with the heating element. However, increasing the amount of thermally conductive filler material reduces the cross-linking density inside the molded body, making it brittle and thus worsening its moldability. Furthermore, while flexibility is necessary to improve gap filling and contact area, excessive flexibility makes it difficult to maintain the shape of the molded body, resulting in poor maneuverability. Thus, improved thermal conductivity and moldability are generally at odds.

[0013] In the thermally conductive molded articles described in the aforementioned patent documents 1 and 2, there is room for improvement from the viewpoint of making both the moldability and thermal conductivity excellent when molded from the thermally conductive composition.

[0014] The present invention is made in view of the above aspects, with the aim of providing a thermally conductive molded article that is molded by a thermally conductive composition with excellent moldability and has excellent thermal conductivity.

[0015] Methods for solving problems

[0016] The inventors conducted in-depth research and found that the above-mentioned problem can be solved by making a thermally conductive molded body containing a polymer matrix and a thermally conductive filler material, and the gel fraction a of the thermally conductive molded body and the content b of the polymer matrix satisfying a specified relationship, thereby completing the present invention.

[0017] The present invention provides the following [1] to

[10] .

[0018] [1] A thermally conductive molded body, characterized in that it comprises a polymer matrix and a thermally conductive filler material. The relationship between the gel fraction a (mass %) of the above thermally conductive molded body and the content b (volume %) of the above polymer matrix satisfies both of the following equations (1) and (2).

[0019] a>1.25×b-4.1 Equation (1)

[0020] a < 2.87 × b - 33 Equation (2)

[0021] (Method for determining gel fraction)

[0022] (1) Immerse about 2g of the thermally conductive molded body in 40g of an organic solvent that can dissolve the resin components other than the gel component for 1 day. Then, take the organic solvent insoluble part of the above thermally conductive molded body, dry it, and calculate the gel fraction using the following formula (3).

[0023] Gel fraction = 100 × X / Y (Equation 3)

[0024] In equation (3), X = (Dried mass of organic solvent-insoluble matter - (Mass of thermally conductive molded body before impregnation × (1 - Ratio of polymer matrix mass when the mass of thermally conductive molded body is set to 1))) Y = (Mass of the thermally conductive molded body before impregnation × Ratio of the mass of the polymer matrix when the mass of the thermally conductive molded body is set to 1) [2] A thermally conductive molded body, characterized in that it comprises a polymer matrix and a thermally conductive filler material. The relationship between the gel fraction a (mass%) of the above thermally conductive molded body and the content b (volume%) of the above polymer matrix satisfies both of the following equations (1) and (2-2).

[0025] a>1.25×b-4.1 Equation (1)

[0026] a < 4.50 × b - 97 Equation (2-2)

[0027] (Method for determining gel fraction)

[0028] (1) Immerse about 2g of the thermally conductive molded body in 40g of an organic solvent that can dissolve the resin components other than the gel component for 1 day. Then, take the organic solvent insoluble part of the above thermally conductive molded body, dry it, and calculate the gel fraction using the following formula (3).

[0029] Gel fraction = 100 × X / Y (Equation 3)

[0030] In equation (3), X = (Dried mass of organic solvent-insoluble matter - (Mass of thermally conductive molded body before impregnation × (1 - Ratio of polymer matrix mass when the mass of thermally conductive molded body is set to 1))) Y = (Mass of the thermally conductive molded body before impregnation × Ratio of the mass of the polymer matrix when the mass of the thermally conductive molded body is set to 1) [3] According to the thermally conductive molded body described in [1] or [2] above, the thermally conductive molded body has a three-dimensional surface with a surface area of ​​1.46 × A or more relative to the projected area A in at least one direction.

[0031] [4] The thermally conductive molded body according to any one of [1] to [3] above, wherein the content of the polymer matrix is ​​17.5 to 50% by volume.

[0032] [5] The thermally conductive molded body according to any one of [1] to [4] above, wherein the content of the thermally conductive filler material is 50 to 82.5% by volume.

[0033] [6] The thermally conductive molded body according to any one of [1] to [5] above, wherein the polymer matrix is ​​a cured body of organopolysiloxane.

[0034] [7] The thermally conductive molded body according to any one of [1] to [6] above, wherein the polymer matrix is ​​a cured body of an addition-reactive organopolysiloxane.

[0035] [8] The thermally conductive molded body according to any one of [1] to [7] above, wherein the thermally conductive filler material comprises at least one selected from aluminum oxide and aluminum hydroxide.

[0036] [9] The thermally conductive molded body according to any one of [1] to [8] above has an E hardness of 3 to 90.

[0037]

[10] The thermally conductive molded body according to any one of [1] to [9] above has a thermal conductivity of 1 W / mK or more.

[0038] The effects of the invention

[0039] According to the present invention, thermally conductive molded articles with excellent thermal conductivity and formability can be provided. Attached Figure Description

[0040] Figure 1 A graph showing the relationship between equation (1) and equation (2).

[0041] Figure 2 A graph showing the relationship between equation (1) and equation (2-2) is provided.

[0042] Figure 3 A diagram illustrating the evaluation of formability. Detailed Implementation

[0043] [Thermetically conductive molded body]

[0044] The thermally conductive molded body of the present invention comprises a polymer matrix and a thermally conductive filler material, and the relationship between the gel fraction a of the thermally conductive molded body and the content b of the polymer matrix satisfies both of the following equations (1) and (2).

[0045] a>1.25×b-4.1 Equation (1)

[0046] a < 2.87 × b - 33 Equation (2)

[0047] It should be noted that the gel fraction a is in mass%, and the content of the polymer matrix b is in volume.

[0048] If one or both of the above formulas (1) and (2) are not satisfied, the formability of the thermally conductive composition deteriorates when it is molded into a 3D shape using a mold or the like.

[0049] The inventors conducted numerous experiments and found that by satisfying both equations (1) and (2) above, the formability becomes good.

[0050] It can be assumed that when the gel fraction is small and equations (1) and (2) are not satisfied, the cross-linking of the polymer matrix becomes sparse, making it difficult to maintain the shape while maintaining the thermal conductivity of the filler material, thus reducing the moldability.

[0051] On the other hand, it can be considered that when the gel fraction is large and equations (1) and (2) are not satisfied, although the cross-linking density of the polymer matrix is ​​high, due to the filling of thermally conductive filler material in large quantities from the point of view of improving thermal conductivity, it lacks toughness and the molded body is prone to damage during demolding, thus reducing its moldability.

[0052] If the diagram satisfies both equations (1) and (2), then as follows Figure 1 That is, if the content of the polymer matrix b and the gel fraction a are adjusted to the region between the line a = 1.25 × b - 4.1 and the line a = 2.87 × b - 33 (... Figure 1 The area marked with the up and down arrows in the middle (the area where the shape becomes good) then the formability becomes good.

[0053] It should be noted that the polymer matrix content b at the intersection of equation (1) and equation (2) is approximately 17.8% by volume. Therefore, in order to satisfy both equation (1) and equation (2), the polymer matrix content needs to be above 17.8% by volume.

[0054] Depend on Figure 1 It is known that the higher the content of the polymer matrix, the wider the range of gel fraction that can be used to obtain thermally conductive molded bodies with good moldability. That is, with a high polymer matrix content, a wide range of gel fractions can be achieved, resulting in greater design freedom.

[0055] On the other hand, when the polymer matrix content is low, the range of gel fractions used to obtain thermally conductive molded bodies with good moldability becomes narrower. That is, when the polymer matrix content is low, the range of gel fractions used to obtain thermally conductive molded bodies with good moldability is narrow, and the gel fraction needs to be strictly adjusted.

[0056] From the viewpoint of obtaining a thermally conductive molded article with excellent thermal conductivity, it is preferable to have a low polymer matrix content (i.e., a high content of thermally conductive filler material). By applying the present invention, even in areas where it is generally difficult to achieve a low polymer matrix content with good moldability, a thermally conductive molded article with excellent moldability can be obtained by setting the gel fraction within a specified range.

[0057] From this perspective, it is preferable to satisfy formulas (1) and (2) in a region where the polymer matrix content is 17.5% or more and 50% or less, more preferably in a region where the polymer matrix content is 20% or more and 50% or less, and even more preferably in a region where the polymer matrix content is 30% or more and 40% or less.

[0058] Other inventions of the present invention involve thermally conductive molded bodies comprising a polymer matrix and a thermally conductive filler material, wherein the gel fraction a of the thermally conductive molded body and the content b of the polymer matrix satisfy both of the following equations (1) and (2-2).

[0059] a>1.25×b-4.1 Equation (1)

[0060] a < 4.50 × b - 97 Equation (2-2)

[0061] It should be noted that the gel fraction a is in mass%, and the content of the polymer matrix b is in volume.

[0062] When both of the above formulas (1) and (2-2) are satisfied, the formability of the thermally conductive composition becomes good when it is molded into a 3D shape using a mold or the like.

[0063] The inventors conducted numerous experiments and found that by satisfying both equations (1) and (2-2) above, the formability becomes good.

[0064] If the diagram satisfies both equations (1) and (2-2), then it is as follows: Figure 2 That is, if the content of the polymer matrix b and the gel fraction a are adjusted to the region between the line a = 1.25 × b - 4.1 and the line a = 4.50 × b - 97 (... Figure 2 The area marked with the up and down arrows in the middle (the area where the shape becomes good) then the formability becomes good.

[0065] It should be noted that the polymer matrix content b at the intersection of equation (1) and equation (2-2) is approximately 28.6% by volume. Therefore, in order to satisfy both equation (1) and equation (2-2), the polymer matrix content needs to be above 28.6% by volume.

[0066] Depend on Figure 2It is known that the higher the content of the polymer matrix, the wider the range of gel fraction that can be used to obtain thermally conductive molded bodies with good moldability. That is, with a high polymer matrix content, a wide range of gel fractions can be achieved, resulting in greater design freedom.

[0067] On the other hand, when the polymer matrix content is low, the range of gel fractions used to obtain thermally conductive molded bodies with good moldability becomes narrower. That is, when the polymer matrix content is low, the range of gel fractions used to obtain thermally conductive molded bodies with good moldability is narrow, and the gel fraction needs to be strictly adjusted.

[0068] From the viewpoint of obtaining a thermally conductive molded article with excellent thermal conductivity, it is preferable to have a low polymer matrix content (i.e., a high content of thermally conductive filler material). By applying the present invention, even in areas where it is generally difficult to achieve a low polymer matrix content with good moldability, a thermally conductive molded article with excellent moldability can be obtained by setting the gel fraction within a specified range.

[0069] From this perspective, the content of the polymer matrix in the thermally conductive molded body is preferably 17.5% or more and 50% or less when the thermally conductive molded body is set to 100% by volume, more preferably 20% or more and 50% or less by volume, even more preferably 30% or more and 40% or less by volume, and even more preferably 30% or more and 35% or less by volume.

[0070] Furthermore, the content of the thermally conductive filler material in the thermally conductive molded article is preferably 50% by volume or more and 82.5% by volume or less when the thermally conductive molded article is set to 100% by volume, more preferably 50% by volume or more and 70% by volume or less. If the content of the thermally conductive filler material is 50% by volume or more, a certain degree of thermal conductivity can be imparted to the thermally conductive molded article. By keeping the content of the thermally conductive filler material at 70% by volume or less, the thermally conductive filler material can be appropriately dispersed in the polymer matrix. In addition, it is also possible to prevent the viscosity of the thermally conductive composition from becoming excessively high. The volume-based content of the thermally conductive filler material is further preferably 60% by volume or more and 70% by volume or less, more preferably 65% ​​by volume or more and 70% by volume or less.

[0071] The gel fraction of thermally conductive molded parts can be adjusted by factors such as the content of the polymer matrix and the crosslinking density of the polymer matrix. For example, a higher polymer matrix content results in a higher gel fraction. Similarly, a higher crosslinking density of the polymer matrix also results in a higher gel fraction.

[0072] In the case of cured bodies of addition-reactive organopolysiloxanes as the polymer matrix, the gel fraction can be adjusted by regulating the ratio (H / Vi) of the addition-reactive organopolysiloxane's main agent to the curing agent. For example, by making H / Vi close to 1, a larger gel fraction can be achieved.

[0073] In addition, the gel fraction can be adjusted according to the type of thermally conductive filler material. For example, the gel fraction can also be adjusted according to the type of surface treatment agent (chain length, etc.) that has been used to treat the thermally conductive filler material.

[0074] The gel fraction of the thermally conductive molded body is not particularly limited as long as it meets the range of the above formulas (1) and (2), for example, it is 35 to 85% by mass, preferably 40 to 70% by mass.

[0075] The gel fraction was determined by the following method.

[0076] (Method for determining gel fraction)

[0077] About 2g of the thermally conductive molded body was immersed in 40g of an organic solvent that could dissolve the resin components other than the gel component for 1 day. Then, the organic solvent-insoluble part of the above thermally conductive molded body was taken, dried, and the gel fraction was calculated by the following formula (3).

[0078] Gel fraction = 100 × X / Y (Equation 3)

[0079] In equation (3), X = (Dried mass of organic solvent-insoluble matter - (Mass of thermally conductive molded body before impregnation × (1 - Ratio of polymer matrix mass when the mass of thermally conductive molded body is set to 1))) Y = (Mass of the thermally conductive molded body before impregnation × Ratio of the mass of the polymer matrix when the mass of the thermally conductive molded body is set to 1) X represents the mass of the thermally conductive filler material included in the dried mass of the organic solvent-insoluble material after removing the dried mass of the organic solvent-insoluble material. Furthermore, Y represents the mass of the polymer matrix in the thermally conductive molded body before impregnation.

[0080] It should be noted that there are no particular limitations on the organic solvent, as long as it can dissolve the resin components other than the gel component. However, when the polymer matrix of the thermally conductive molded part is an organosilicon matrix, toluene is preferred.

[0081] <Three-dimensional shape>

[0082] The thermally conductive molded body of the present invention can be in the shape of a sheet or a plate, but preferably has a three-dimensional shape. That is, in order to improve the adaptability of the thermally conductive molded body of the present invention to heat-generating and heat-dissipating bodies with complex shapes, it is preferable that the shape is not a flat sheet or plate. For example, in a plate-shaped molded body, one or two surfaces form height differences, protrusions, depressions, grooves, etc., resulting in a non-flat shape.

[0083] The thermally conductive molded body of the present invention preferably comprises, when the projected area confirmed in at least one direction is set as A, a three-dimensional surface with a surface area in one direction preferably of 1.20A or more, more preferably 1.46A or more, and even more preferably 2.10A or more.

[0084] In this invention, by satisfying the above formulas (1) and (2), a thermally conductive molded body having the above-mentioned three-dimensional surface can be formed with good formability.

[0085] <Polymer Matrix>

[0086] The polymer matrix is ​​a polymer compound such as an elastomer or rubber, and preferably a substance formed by curing a liquid resin component consisting of a mixture of a main agent and a curing agent. The resin component can be, for example, a substance composed of uncrosslinked rubber and a crosslinking agent, or a substance containing monomers, prepolymers, and a curing agent. Furthermore, the curing reaction can be performed at room temperature or by heat curing.

[0087] As polymer matrices, various matrices can be used, such as silicone matrices, epoxy matrices, urethane matrices, phenol matrices, unsaturated polyester matrices, polyimide matrices, acrylic matrices, polyamide matrices, polyether matrices, polybutadiene matrices, polyisopropylene matrices, polyisobutylene matrices, ethylene-propylene-diene matrices, natural rubber matrices, silyl-modified polyether matrices, and matrices combining these. In particular, silicone matrices are preferred among polymer matrices.

[0088] In thermally conductive molded bodies, when the polymer matrix is ​​an organosilicon matrix, the organosilicon matrix is ​​preferably a cured body of organopolysiloxane, and is preferably formed by a resin component containing organopolysiloxane.

[0089] Furthermore, the thermally conductive molded body is preferably formed from a thermally conductive composition containing a resin component and a thermally conductive filler material. The resin component preferably comprises an organopolysiloxane.

[0090] The polymer matrix is ​​more preferably a cured form of an addition-reactive organopolysiloxane. The addition-reactive organopolysiloxanes preferably include organopolysiloxanes containing alkenyl groups and organopolysiloxanes containing hydroxymethylsilyl groups.

[0091] Furthermore, the thermally conductive molded articles, as described in the thermally conductive compositions described later, may appropriately contain components (additives, etc.) other than thermally conductive fillers and silicone matrix.

[0092] An alkenyl-containing organopolysiloxane is an organopolysiloxane with an alkenyl group. The alkenyl group can be present in the side chain, at the terminal, or both. An alkenyl-containing organopolysiloxane can be used alone or in combination with two or more.

[0093] If an organopolysiloxane with alkenyl groups in the side chain is used (organopolysiloxane containing alkenyl groups in the side chain), the gel fraction is more easily increased even when the ratio (H / Vi) of silyl groups contained in the resin component to alkenyl groups contained in the resin component is the same.

[0094] If an organopolysiloxane containing side-chain alkenyl groups is used, the resulting polymer matrix will be in a state of near-uniform dispersion of crosslinking points. The molecular weight of the crosslinking points will be relatively larger, thereby suppressing the increase in local hardness and imparting a softness that is difficult to achieve with previous configurations, even at the crosslinking points.

[0095] Organopolysiloxanes containing side-chain alkenyl groups can be linear, branched, or a mixture of linear and branched forms, but are preferably linear. The alkenyl groups in the side chains refer to those contained outside the ends of the molecular chains in the polysiloxane structure.

[0096] In addition, organopolysiloxanes containing side-chain alkenyl groups can also be substances that have alkenyl groups at the ends in addition to the side chains, but it is preferred that they have alkenyl groups only in the side chains.

[0097] The organopolysiloxane containing side-chain alkenyl groups is preferably liquid at 25°C. The viscosity of the organopolysiloxane containing side-chain alkenyl groups at 25°C is preferably 50,000 mPas or less, more preferably 10,000 mPas or less, and even more preferably 3,000 mPas or less. By keeping the viscosity of the organopolysiloxane containing side-chain alkenyl groups below the upper limit, it is possible to prevent a decrease in reactivity or a high viscosity in the thermally conductive composition.

[0098] Furthermore, the viscosity of the organopolysiloxane containing side-chain alkenyl groups at 25°C is preferably 50 mPas or more, more preferably 100 mPas or more, and even more preferably 200 mPas or more. By ensuring that the viscosity of the organopolysiloxane containing side-chain alkenyl groups is at or above the aforementioned lower limit, it is possible to prevent the crosslinking density from becoming too high, thus avoiding a low hardness after curing. In addition, it prevents excessively rapid reactivity, thus facilitating an appropriate addition reaction.

[0099] It should be noted that the viscosity was measured according to JIS K7117-1 using a Brookfield Type B viscometer. Furthermore, the rotor in the Brookfield Type B viscometer should preferably be selected with a torque between 10% and 80%.

[0100] The organopolysiloxane containing alkenyl groups preferably has one or more alkenyl groups, but more preferably has two or more alkenyl groups.

[0101] If we define the weight-average molecular weight (g / mol) as Mw and the alkenyl concentration (μmol / g) as C, then the average number of alkenyl groups per molecule can be calculated by Mw × C × 10. -6 The formula is used to calculate the number of alkenyl groups. The average number of alkenyl groups calculated in this way is preferably 2 or more, more preferably 2.2 or more, and even more preferably 2.4 or more. By making the average number of alkenyl groups 2 or more, a cross-linking structure can be appropriately introduced, maintaining hardness, thermal conductivity, etc., while easily achieving lower compressive stress. Furthermore, the average number of alkenyl groups is, for example, only 5 or less, but preferably 4 or less, more preferably 3.5 or less, and even more preferably 3 or less.

[0102] The weight-average molecular weight (Mw) of the alkenyl-containing organopolysiloxane is preferably 5,000 or more and 100,000 or less, more preferably 10,000 or more and 50,000 or less, and even more preferably 15,000 or more and 35,000 or less. By keeping the weight-average molecular weight of the alkenyl-containing organopolysiloxane below the upper limit, it is possible to prevent a decrease in reactivity or a high viscosity in the thermally conductive composition.

[0103] Furthermore, by ensuring that the weight-average molecular weight of the alkenyl-containing organopolysiloxane is above the aforementioned lower limit, the crosslinking density is prevented from becoming too high, thus easily ensuring the flexibility after curing. Additionally, excessively rapid reactivity is prevented, facilitating proper addition reactions. The weight-average molecular weight can be determined by gel permeation chromatography (GPC).

[0104] The functional group concentration of the alkenyl-containing organopolysiloxane is preferably 1 μmol / g or more and 5000 μmol / g or less. If the functional group concentration is 1 μmol / g or more, the amount of alkenyl groups becomes more than a certain level, and a cross-linked structure can be appropriately formed. On the other hand, if the functional group concentration is 5000 μmol / g or less, the cross-linking density is prevented from becoming too high, and the flexibility after curing is easily ensured.

[0105] The functional group concentration of the alkenyl-containing organopolysiloxane is more preferably 20 μmol / g or more and 1000 μmol / g or less, and even more preferably 50 μmol / g or more and 400 μmol / g or less.

[0106] It should be noted that the functional group concentration (μmol / g) refers to the concentration of alkenyl groups in organopolysiloxanes containing alkenyl groups, typically the vinyl group concentration. The functional group concentration can be calculated from the integral ratio of the 1H-NMR spectrum measured using an NMR measuring apparatus.

[0107] The alkenyl group in organopolysiloxanes containing an alkenyl group is not particularly limited, and examples include alkenyl groups with 2 to 8 carbon atoms, such as vinyl, allyl, butenyl, pentenyl, hexenyl, heptenyl, and octenyl. Among these, vinyl is preferred from the viewpoint of ease of synthesis and reactivity. Furthermore, it is preferable that the double bond in the alkenyl group is located at the end of the alkenyl group. In addition, it is preferable that the alkenyl group is directly bonded to a silicon atom.

[0108] Examples of residual groups bonded to silicon atoms, other than the alkenyl group, include alkyl groups such as methyl, ethyl, propyl, butyl, hexyl, and dodecyl, aryl groups such as phenyl, 2-phenylethyl, and 2-phenylpropyl, and further examples include substituted hydrocarbon groups such as chloromethyl and 3,3,3-trifluoropropyl. Among these, hydrocarbon groups are preferred, and methyl is more preferred from the viewpoint of ease of synthesis. Furthermore, it is preferable that 80 mol% or more of the residual groups bonded to silicon atoms are methyl, more preferably 90 mol% or more, and even more preferably 100 mol% are methyl. It should be noted that the organopolysiloxane containing the alkenyl group does not have hydrogen atoms as residual groups bonded to silicon atoms; that is, it is preferable that the organopolysiloxane containing the alkenyl group does not contain hydrosilyl groups.

[0109] The content of the alkenyl-containing organopolysiloxane can be appropriately selected as long as the H / Vi can be adjusted to the desired range as described below, and there is no particular limitation. However, relative to the total amount of organopolysiloxane contained in the thermally conductive composition used to form the thermally conductive molded body, it is preferably 25% by mass or more and 95% by mass or less, more preferably 30% by mass or more and 90% by mass or less.

[0110] (Organopolysiloxanes containing silane groups)

[0111] The resin composition, as described above, contains organopolysiloxanes with silane groups.

[0112] The thermally conductive composition comprises an organopolysiloxane containing silyl groups, which undergoes an addition reaction with an alkenyl-containing organopolysiloxane to extend the chain, thereby forming a cured product with moderate hardness.

[0113] Organopolysiloxanes containing silane groups preferably have at least two functional silane groups. Having at least two functional silane groups allows for proper curing of the thermally conductive composition, and further, introduces a cross-linking structure into the cured product.

[0114] The organopolysiloxane containing hydrosilyl groups can be linear or branched, can contain cyclic structures, or can be a mixture of two or more of them, but it is preferred to contain linear organopolysiloxanes containing hydrosilyl groups.

[0115] Straight-chain or branched organopolysiloxanes containing silanes may contain silanes at the ends or side chains of the molecular chain of the polysiloxane structure, or both at the ends and side chains, but preferably at least at the ends, and more preferably at both ends of the molecular chain of the polysiloxane structure.

[0116] The number of functional groups (the number of silane groups per molecule) in the linear or branched organopolysiloxane containing hydrosilyl groups is preferably 2 to 25, more preferably 3 to 20. It is preferable that the organopolysiloxane containing hydrosilyl groups is liquid at 25°C.

[0117] The organopolysiloxane containing hydrosilyl groups may contain organopolysiloxanes with cyclic structures containing hydrosilyl groups, but the content only needs to be small, for example, 0.01% to 1% by mass of the resin component, preferably 0.03% to 0.5% by mass. However, the organopolysiloxanes with cyclic structures containing hydrosilyl groups only need to be substances with a high functional group concentration (i.e., hydrosilyl group concentration). Specifically, it is sufficient to use substances with a concentration of about 1000 μmol / g to about 20000 μmol / g, preferably substances with a concentration of 2000 μmol / g to 10000 μmol / g.

[0118] In organopolysiloxanes containing silane groups, examples of the remaining groups bonded to silicon atoms besides the silane group include alkyl groups such as methyl, ethyl, propyl, butyl, hexyl, and dodecyl, aryl groups such as phenyl, 2-phenylethyl, and 2-phenylpropyl, and further examples include substituted hydrocarbon groups such as chloromethyl and 3,3,3-trifluoropropyl. Among these, methyl is preferred from the viewpoint of ease of synthesis. Furthermore, it is preferable that 80 mol% or more of the remaining groups bonded to silicon atoms are methyl, more preferably 90 mol% or more, and even more preferably 100 mol% methyl. It should be noted that organopolysiloxanes containing silane groups do not have an alkenyl group as a remaining group bonded to silicon atoms; that is, it is preferable that organopolysiloxanes containing silane groups do not contain an alkenyl group.

[0119] Organopolysiloxanes containing silanes can be used alone or in combination with two or more.

[0120] The weight-average molecular weight (Mw) of the organopolysiloxane containing silane is preferably 3,000 or more and 50,000 or less, more preferably 5,000 or more and 20,000 or less, and more preferably 10,000 or more and 15,000 or less.

[0121] By keeping the weight-average molecular weight of the organopolysiloxane containing silanes below the upper limit, it is possible to prevent a decrease in reactivity or a change in the viscosity of the thermally conductive composition.

[0122] Furthermore, by ensuring that the weight-average molecular weight of the organopolysiloxane containing silane is above the aforementioned lower limit, the crosslinking density is prevented from becoming too high, thus making it easier to ensure the flexibility after curing.

[0123] The content of the organopolysiloxane containing silane can be appropriately selected, for example, as long as the H / Vi can be adjusted to the desired range as described below, and is not particularly limited. However, relative to the total amount of organopolysiloxane contained in the thermally conductive composition, it is preferably 4% by mass or more and 74% by mass or less, more preferably 9% by mass or more and 69% by mass or less.

[0124] Regarding the content of the alkenyl-containing organopolysiloxane and the content of the hydrosilyl-containing organopolysiloxane, the ratio (H / Vi) of the hydrosilyl group contained in the resin component to the alkenyl group contained in the resin component is preferably 0.3 or more and 1.5 or less, more preferably 0.4 or more and 1.0 or less, on a molar basis. By adjusting to such a range, it is easy to satisfy formulas (1) and (2), and it is easy to obtain a thermally conductive molded article with excellent moldability.

[0125] It should be noted that H / Vi can be calculated from the concentrations of silyl groups and alkenyl groups of each component, as well as the content of each component. Furthermore, the concentrations of silyl groups and alkenyl groups of each component can be calculated from the integral ratio of 1H-NMR spectra measured using an NMR spectrometer.

[0126] (Other resin components)

[0127] The thermally conductive composition may contain organopolysiloxanes other than those containing silyl groups and those containing alkenyl groups (also known as other organopolysiloxanes). Specifically, examples include silicone oils, organopolysiloxanes having at least one alkoxy group (organopolysiloxanes containing alkoxy groups), organopolysiloxanes having at least one hydroxyl group (organopolysiloxanes containing hydroxyl groups), and organopolysiloxanes having aromatic structures such as pyrene and perylene, preferably polycyclic aromatic structures (organopolysiloxanes containing aromatic groups).

[0128] In addition to linear silicone oils such as dimethyl silicone oil and phenylmethyl silicone oil, other examples of non-reactive modified silicone oils include those with non-reactive organic groups introduced into the main chain having a polysiloxane structure, the side chains bonded to the main chain, or the ends of the main chain. The term "non-reactive organic group" refers to an organic group that does not have an addition reaction group. Examples of non-reactive modified silicone oils include, for example, polyether-modified silicone oils, aralkyl-modified silicone oils, fluoroalkyl-modified silicone oils, long-chain alkyl-modified silicone oils, higher fatty acid ester-modified silicone oils, higher fatty acid amide-modified silicone oils, and phenyl-modified silicone oils. Among these, linear silicone oils are preferred, and among linear silicone oils, dimethyl silicone oil is more preferred.

[0129] Silicone oil can be used alone or in combination with two or more types.

[0130] The alkoxy-containing organopolysiloxane can be linear, branched, or a mixture of linear and branched forms, but linear is preferred. Furthermore, as the alkoxy-containing organopolysiloxane, any organopolysiloxane having at least one alkoxy group is acceptable, but organopolysiloxanes with at least one alkoxy group at the end of the molecular chain of the polysiloxane structure are preferred, and organopolysiloxanes with at least one alkoxy group at only one end are more preferred. It is presumed that the alkoxy-containing organopolysiloxane, by having alkoxy groups, especially at the ends, readily reacts or interacts with functional groups present on the surface of the thermally conductive filler material, and combines with the polysiloxane structure, thereby reducing the friction of the filler material and facilitating a reduction in the viscosity of the thermally conductive composition.

[0131] The organopolysiloxane containing alkoxy groups preferably has the group shown in formula (4), which is preferably linked to Si constituting the polysiloxane structure via a linker.

[0132] -SiR 1 a (OR 2 3-a (4)

[0133] (It should be noted that in equation (4), R) 1 R 2 Each is independently a hydrocarbon group, preferably an alkyl group. R 1 R 2 The number of carbon atoms is, for example, 1 to 8, but preferably 1 to 4, more preferably 1 or 2. 1 R 2 Preferred examples are methyl and ethyl. (a is an integer from 0 to 2, preferably 0 or 1, more preferably 0.)

[0134] The linker group connecting the group shown in formula (4) to Si is any one of an oxygen atom, a divalent hydrocarbon group, or an ester structure, preferably a divalent hydrocarbon group. Examples of divalent hydrocarbon groups include those with approximately 1 to 8 carbon atoms, such as methylene, ethylene, propylene, butylene, and methyl ethylene, with ethylene being the most preferred.

[0135] The organopolysiloxane containing alkoxy groups has a siloxane backbone (-Si-O-), wherein the number of repeating units n of the siloxane backbone is, for example, 10 or more and 320 or less, preferably 20 or more and 280 or less, and more preferably 25 or more and 230 or less.

[0136] Organopolysiloxanes containing hydroxyl groups may have only one hydroxyl group or more than two hydroxyl groups. It should be noted that there is no particular upper limit to the number of hydroxyl groups, but it is preferable to have 6 or fewer hydroxyl groups, and more preferably 3 or fewer.

[0137] Organopolysiloxanes containing hydroxyl groups readily react or interact with functional groups on the surface of thermally conductive fillers, thereby improving the dispersibility of the thermally conductive fillers and facilitating the reduction of the viscosity of the composition.

[0138] The number of hydroxyl groups in an organopolysiloxane can be one, and it is preferred to have an organopolysiloxane with a hydroxyl group at one end of the main chain.

[0139] It should be noted that the hydroxyl group can be directly bonded to the end of the organopolysiloxane chain, but it is preferred to bond via a linker. A single hydroxyl group can bond to one Si via a linker, or multiple hydroxyl groups (e.g., two or three) can bond to one Si via a linker. The linker can be a hydrocarbon group containing ester bonds, amide bonds, ether bonds, oxime ester bonds (-C=NOC(=O)-), etc., and is preferably a hydrocarbon group with an ether bond. The linker has approximately 1 to 20 carbon atoms, but is preferably 2 to 15, and more preferably 3 to 10.

[0140] The organopolysiloxane with hydroxyl groups of the present invention has a siloxane backbone (-Si-O-), wherein the number of repeating units n of the siloxane backbone is preferably 11 or more and 350 or less, more preferably 20 or more and 300 or less, and even more preferably 50 or more and 270 or less.

[0141] It should be noted that the specific descriptions of the remaining groups bonded to silicon atoms in organopolysiloxanes containing alkoxy groups and organopolysiloxanes containing hydroxyl groups are the same as those for organopolysiloxanes containing alkenyl groups, and therefore their descriptions are omitted.

[0142] In addition, organopolysiloxanes containing alkoxy groups, organopolysiloxanes containing hydroxyl groups, or organopolysiloxanes containing aromatic groups are preferably organopolysiloxanes that are liquid at 25°C.

[0143] The content of other organopolysiloxanes in the resin composition is not particularly limited, for example, it is 0.1% by mass or more and 12% by mass or less, preferably 0.5% by mass or more and 10% by mass or less.

[0144] Furthermore, the thermally conductive composition may contain resin components other than organopolysiloxanes as long as it achieves the effects of the present invention. However, it is preferable that organopolysiloxanes are the main component in the resin composition. Specifically, the content of organopolysiloxanes relative to the total resin composition is, for example, 70% by mass or more and 100% by mass or less, preferably 80% by mass or more and 100% by mass or less, more preferably 90% by mass or more and 100% by mass or less, and even more preferably 100% by mass. That is, the resin composition preferably does not contain resin components other than organopolysiloxanes.

[0145] The resin content in the thermally conductive composition is preferably 30% by volume or more and 50% by volume or less. That is, the polymer matrix content in the thermally conductive molded article is preferably 30% by volume or more and 50% by volume or less. By having a content of 30% by volume or more, the thermally conductive filler material can be appropriately retained through the polymer matrix after curing. Furthermore, by having a content of 50% by volume or less, it is easy to include components other than the polymer matrix, such as thermally conductive filler material, in the thermally conductive molded article. By including more thermally conductive filler material, it is easier to improve the thermal conductivity. The resin content in the thermally conductive composition (i.e., the polymer matrix content of the thermally conductive molded article) is more preferably 30% by volume or more and 40% by volume or less, and even more preferably 30% by volume or more and 35% by volume or less.

[0146] [Thermal conductive filler material]

[0147] Examples of thermally conductive filler materials include, for example, metals, metal oxides, metal nitrides, metal hydroxides, carbon materials, oxides, nitrides, carbides, and organic fibers other than metals. Furthermore, thermally conductive filler materials can be in the form of spheres or amorphous powders.

[0148] In thermally conductive filler materials, metals such as aluminum, copper, and nickel can be cited. Metal oxides such as aluminum oxide (represented by aluminum oxide), magnesium oxide, and zinc oxide can be cited. Metal nitrides such as aluminum nitride can be cited. Metal hydroxides such as aluminum hydroxide can be cited. Furthermore, carbon materials such as spherical graphite and diamond can be cited. Oxides, nitrides, and carbides other than metals can be cited, such as quartz, boron nitride, and silicon carbide.

[0149] Examples of organic fibers include poly(p-phenylene benzo[a]). Azole fiber.

[0150] Among these, metal oxides, metal nitrides, metal hydroxides, and carbon materials are preferred as thermally conductive filler materials from the viewpoint of improving thermal conductivity, with metal oxides or metal hydroxides being more preferred. Furthermore, specifically, aluminum oxides, aluminum hydroxide, and boron nitride are preferred as thermally conductive filler materials, with aluminum oxides and aluminum hydroxide being more preferred, and at least one selected from aluminum oxides and aluminum hydroxide being more preferred.

[0151] Among them, aluminum oxide is preferred from the viewpoint of improving the heat dissipation of the thermally conductive molded article. Furthermore, aluminum hydroxide is preferred when it is desirable to improve flame retardancy and reduce the weight of the inorganic filler to achieve a lighter thermally conductive resin composition.

[0152] These thermally conductive filler materials can be used alone or in combination of two or more.

[0153] The average particle size of the thermally conductive filler material is not particularly limited, but is preferably 0.1 to 200 μm, more preferably 0.3 to 100 μm, and even more preferably 0.5 to 70 μm.

[0154] The thermally conductive filler material preferably combines two or more materials with different average particle sizes, and more preferably combines a small-particle-size thermally conductive filler material with an average particle size of 0.1 μm or more and 5 μm or less with a large-particle-size thermally conductive filler material with an average particle size of more than 5 μm and 200 μm or less.

[0155] Furthermore, a preferred approach is to use a thermally conductive filler with a first-largest particle size (average particle size greater than 5 μm and less than 20 μm) and a second-largest particle size (average particle size greater than 20 μm and less than 200 μm).

[0156] It should be noted that the average particle size of the thermally conductive filler material is D50, which can be calculated by observing the thermally conductive filler material under a microscope and using the major axis as the diameter. More specifically, it refers to the particle size corresponding to more than 500 major axes of any particle, equivalent to 50% of the cumulative frequency, measured using, for example, an electron microscope or optical microscope. Specifically, using the thermally conductive filler material as a sample, the particle size distribution curve can be obtained by setting the horizontal axis to particle size and the vertical axis to cumulative frequency. This particle size distribution curve is a number-based particle size distribution curve obtained by accumulating the particle sizes of the thermally conductive filler materials with small particle sizes. It should be noted that it is preferable to measure the major axis of the particle size; for example, for the fiber materials described later, it is sufficient to measure the length along the major axis.

[0157] Thermally conductive fillers can be surface-treated using surface treatment agents such as silane coupling agents. Surface-treated thermally conductive fillers can be obtained by mixing the surface treatment agent with the thermally conductive filler. Furthermore, from the viewpoint of facilitating surface treatment, wet treatment methods, dry treatment methods, etc., are preferred when mixing.

[0158] For wet treatment methods, it is preferable to mix a thermally conductive filler material into a solution in which a surface treatment agent is dispersed or dissolved, and then heat the solution to allow the surface treatment agent to bond or adhere to the surface of the thermally conductive filler material. Dry treatment methods are surface treatment methods that do not use solutions. Specifically, this involves mixing a thermally conductive filler material with a surface treatment agent, stirring it with a mixer or similar device, and then heating the solution to allow the surface treatment agent to bond or adhere to the surface of the thermally conductive filler material.

[0159] Examples of surface treatment agents include silane coupling agents and fatty acids. As silane coupling agents, known substances are used without particular restriction, and examples include, for instance, dimethyldimethoxysilane, 3-acryloyloxypropyltrimethoxysilane, 3-methacryloyloxypropyltrimethoxysilane, vinyltrimethoxysilane, n-decyltrimethoxysilane, 3-isocyanate-propyltriethoxysilane, 3-(2-aminoethyl)aminopropyltrimethoxysilane, 3-mercaptopropyltrimethoxysilane, epoxypropoxypropyltrimethoxysilane, and 3-phenylaminopropyltrimethoxysilane. Furthermore, alkenyltriethoxysilanes with approximately 8 to 18 carbon atoms in the alkenyl group, such as octenyltrimethoxysilane, can also be used.

[0160] Furthermore, fatty acids can be either liquid at room temperature (25°C) or solid at room temperature. Examples of liquid fatty acids include saturated fatty acids such as butyric acid, valeric acid, hexanoic acid, heptanoic acid, caprylic acid, and nonanoic acid, as well as unsaturated fatty acids such as myristone acid, palmitoleic acid, ricinoleic acid, oleic acid, linoleic acid, and linolenic acid.

[0161] Examples of solid fatty acids include saturated fatty acids with approximately 10 to 24 carbon atoms, such as decanoic acid, palmitic acid, and stearic acid, as well as unsaturated fatty acids such as crotonic acid and sorbic acid. Among these, stearic acid is preferred.

[0162] A single surface treatment agent can be used alone, or two or more can be used together.

[0163] Furthermore, surface treatment using surface treatment agents such as silane coupling agents can be carried out through a bulk blending method. Therefore, surface treatment agents such as silane coupling agents can be mixed into the resin composition, and the thermally conductive filler material can be surface-treated by the silane coupling agents and fatty acids mixed into the resin composition.

[0164] (Other additives)

[0165] Various additives may be included in the thermally conductive composition used to form the thermally conductive molded article of the present invention. Examples of additives include, for instance, curing catalysts, reaction control agents, dispersants, flame retardants, plasticizers, antioxidants, colorants, surface treatment agents, thixotropic agents, etc.

[0166] In the above-mentioned thermally conductive composition, it is preferable to contain a curing catalyst. The curing catalyst need only be a catalyst that promotes the addition reaction between an alkenyl-containing organopolysiloxane and a silyl-containing polysiloxane. By containing a curing catalyst, the thermally conductive composition can be properly cured and crosslinked.

[0167] Platinum group-based curing catalysts can be cited as examples of curing catalysts. There are no particular limitations on platinum group-based curing catalysts; examples include chloroplatinic acid, coordination compounds of chloroplatinic acid with olefins, vinylsiloxanes, or acetylene compounds, etc. The content of the platinum group-based curing catalyst in the thermally conductive composition is not particularly limited, as long as it contains an amount sufficient to promote the addition reaction. For example, it is 0.0001 to 1 part by mass relative to 100 parts by mass of the organopolysiloxane contained in the thermally conductive composition, preferably 0.001 to 0.5 parts by mass.

[0168] [Single-liquid or two-liquid thermally conductive compositions]

[0169] The thermally conductive composition of this invention can be a single-liquid composition or a two-liquid composition consisting of a first agent and a second agent. In the two-liquid composition, the first agent and the second agent are mixed to obtain the thermally conductive composition during use.

[0170] It should be noted that, in the case of a two-component composition, it is preferable to appropriately distribute each component of the thermally conductive composition into the first agent and the second agent. For example, in a two-component thermally conductive composition, the first agent preferably contains an alkenyl-containing organopolysiloxane and a curing catalyst, but preferably does not contain an alkyl-containing organopolysiloxane. In this case, the second agent preferably contains an alkyl-containing organopolysiloxane, but does not contain a curing catalyst. Furthermore, the second agent may further contain an alkenyl-containing organopolysiloxane.

[0171] Furthermore, it is preferable that at least one of the first agent and the second agent contains a thermally conductive filler material, but it is even more preferable that both the first agent and the second agent contain a thermally conductive filler material.

[0172] In addition, it is preferable that other organopolysiloxanes, other resin components and additives are appropriately allocated to the first and second agents.

[0173] A single-liquid thermally conductive composition can be obtained by appropriately mixing the components constituting the thermally conductive composition. Furthermore, a two-liquid thermally conductive composition can be obtained by separately mixing the components constituting the first agent and the second agent to prepare the first agent and the second agent, and then mixing the first agent and the second agent. The method for obtaining the thermally conductive composition by mixing the first agent and the second agent is not limited, and methods such as static mixers, mixers with stirring blades, vibratory mixers, and rotary mixers can be used.

[0174] [Physical properties of thermally conductive molded parts]

[0175] (E hardness)

[0176] The E hardness of the thermally conductive molded body of the present invention is preferably 3 or higher and 90 or lower. If the E hardness is 90 or lower, the hardness of the thermally conductive molded body will not become excessively high, and it can be used in thermally conductive molded bodies with three-dimensional shapes. Furthermore, by making the E hardness 3 or higher, excessively low hardness can be prevented.

[0177] The E hardness is preferably 70 or less, more preferably 50 or less, and even more preferably 30 or less. When the thermally conductive molded body has such a low E hardness, the thermally conductive molded body has high flexibility and improved conformability to heat-generating elements, etc. Furthermore, due to its ease of compression, its operability is improved. In other words, the molded body of the present invention, possessing a low E hardness, exhibits excellent operability, thermal conductivity, and moldability.

[0178] From the viewpoint of preventing excessive softness and ensuring a certain degree of formability, the E hardness is more preferably 5 or higher, and even more preferably 10 or higher.

[0179] It should be noted that E hardness refers to the E type hardness specified in JIS K6253.

[0180] (OO hardness)

[0181] Furthermore, the hardness of the thermally conductive molded body of the present invention is not particularly limited, but is preferably 15 or more, more preferably 20 or more, even more preferably 30 or more, and preferably 80 or less, more preferably 75 or less, even more preferably 70 or less, and even more preferably 60 or less.

[0182] It should be noted that OO type hardness is determined by the method specified in ASTM D2240.

[0183] (thermal conductivity)

[0184] The thermal conductivity of the thermally conductive molded body of the present invention is preferably 1.0 W / (m²). K) or higher. If the thermal conductivity of the molded body is 1.0 W / (m²), then... A thermal conductivity of 1.5 W / (m²) or higher ensures good heat dissipation, adequately guaranteeing the heat dissipation required for thermally conductive molded bodies, for example, those with three-dimensional shapes. From the viewpoint of further improving heat dissipation, a thermal conductivity of 1.5 W / (m²) is more preferable. K) or higher, more preferably 2.0 W / (m The upper limit for thermal conductivity is not specifically limited, but in practical applications it is, for example, 30 W / (m²). K) or less, more preferably 10W / (m K) and below.

[0185] (Flame retardancy)

[0186] The flame retardancy of the thermally conductive molded body of the present invention is preferably V-1 or higher in the UL94 standard, and more preferably V-0.

[0187] It should be noted that the flame retardancy of V-1 can be achieved by containing a specified amount of thermally conductive filler material in the silicone matrix. If substances that can impart flame retardancy, such as aluminum hydroxide, are used as thermally conductive fillers, the flame retardancy of V-0 can also be achieved.

[0188] [Manufacturing method of thermally conductive molded body]

[0189] Thermally conductive molded articles can be obtained by curing thermally conductive compositions. Preferably, the thermally conductive molded article of the present invention is formed by casting the thermally conductive composition into a molding die or similar mold, resulting in a three-dimensional shape that conforms to the shape of the molding die. The thermally conductive molded article of the present invention exhibits excellent formability because it satisfies formulas (1) and (2) as described above.

[0190] There are no particular limitations on the method of molding a thermally conductive composition into a thermally conductive molded body with a three-dimensional shape, and examples include compression molding, injection molding, and transfer molding.

[0191] The shape of the thermally conductive molded body with a three-dimensional shape is not particularly limited, but it is preferable to have a shape that matches the shape of the heat sink or heat source to be applied, and it may have appropriate concave or convex parts.

[0192] Furthermore, the curing conditions for curing the thermosetting composition are not particularly limited. For example, it can be cured by heating at 80°C or higher and 200°C or lower for 30 seconds or more and 30 minutes or less, preferably by heating at 100°C or higher and 160°C or lower for 1 minute or more and 15 minutes or less. Typically, it is cured at 125°C for 8 minutes. Furthermore, after curing to the aforementioned three-dimensional shape, a second curing can be performed. For example, a second curing can be performed by heating at 150°C or higher and 200°C or lower for 24 hours or less. Furthermore, a second curing is preferably performed at 120°C to 180°C for 1 to 6 hours.

[0193] However, the thermally conductive molded body does not necessarily need to be a three-dimensional thermally conductive molded body; it can be a block-shaped thermally conductive molded body or a sheet-shaped thermally conductive molded body. Block-shaped and sheet-shaped thermally conductive molded bodies are preferably manufactured by curing the thermally conductive composition under the aforementioned curing conditions. Furthermore, sheets can be produced by slicing or other methods after curing the thermally conductive composition.

[0194] Furthermore, when thermally conductive molded bodies contain anisotropic filler materials, the anisotropic filler materials can be oriented in one direction. It should be noted that anisotropic filler materials include fibrous materials, flake-like materials, etc., with flake-like materials being preferred. The anisotropic filler materials have a high aspect ratio, specifically, an aspect ratio exceeding 2.

[0195] By orienting anisotropic filler materials along one direction, thermal conductivity in one direction can be easily improved in thermally conductive molded articles. For example, in order to improve thermal conductivity in the thickness direction of sheet-like thermally conductive molded articles, it is preferable to orient anisotropic filler materials along the thickness direction as described above.

[0196] The following describes a manufacturing method for orienting anisotropic filler materials, using a method for obtaining a sheet-like thermally conductive molded body in which anisotropic filler material is oriented along the thickness direction as an example.

[0197] One embodiment of the manufacturing method of the thermally conductive molded body includes the following steps (A) and (B).

[0198] Process (A): The process of obtaining an oriented molded body in which anisotropic filler material is oriented in one direction.

[0199] Process (B): The process of cutting the oriented molded body into sheet-like pieces to obtain sheet-like molded bodies.

[0200] The following is a more detailed explanation of each process.

[0201] [Process (A)]

[0202] In process (A), an oriented molded body is formed from a thermally conductive composition. It is preferable that the thermally conductive composition is cured to become an oriented molded body. Furthermore, the oriented molded body is a material in which anisotropic filler material is oriented along a direction that forms the thickness direction in the thermally conductive sheet. More specifically, the oriented molded body can be obtained through magnetic field orientation methods, flow orientation methods, etc.

[0203] (Magnetic field orientation method)

[0204] In the magnetic field orientation method, an oriented molded body is obtained by injecting a thermally conductive composition into the interior of a molding die or similar mold and then placing it in a magnetic field. This causes the anisotropic filler material to be oriented along the magnetic field, and the thermally conductive composition is then cured. The oriented molded body is preferably a block-shaped material.

[0205] Furthermore, a release film can be disposed inside the molding die, at the portion of the molding die that contacts the mixing composition. The release film may be, for example, a resin film with good release properties, or a resin film that has undergone a release treatment on one side with a release agent. By using the release film, the oriented molded body is easily demolded from the mold.

[0206] It should be noted that the curing of the thermally conductive composition in the magnetic field orientation method is preferably carried out under the curing conditions described above.

[0207] For magnetic field orientation, the viscosity of the thermally conductive composition used in the magnetic field orientation process is preferably 10–300 Pa. s. By 10 Pa Above s, thus the filling materials are less prone to settling. Furthermore, by providing 300Pa... The viscosity is below s, resulting in good flowability. In a magnetic field, the anisotropic filler material is properly oriented without the undesirable situation of excessively timed orientation. It should be noted that the viscosity referred to here is the viscosity measured using a rotational viscometer (Brookfield DV-E, rotor SC4-14) at 25°C and a rotational speed of 10 rpm. However, when using filler materials that do not easily settle, or when incorporating additives such as anti-settling agents, the viscosity of the thermally conductive composition can be less than 10 Pa. s.

[0208] In magnetic field orientation manufacturing methods, examples of magnetic field line generators for applying magnetic field lines include superconducting magnets, permanent magnets, and electromagnets. However, superconducting magnets are preferred in terms of generating magnetic fields with high magnetic flux density. The magnetic flux density of the magnetic field generated by these magnetic field line generators is preferably 1 to 30 Tesla. If the magnetic flux density is 1 Tesla or higher, it is easier to orient anisotropic filling materials. Furthermore, by setting it to 30 Tesla or lower, it can be manufactured in a practical manner.

[0209] (Flow-oriented manufacturing method)

[0210] For the flow orientation method, firstly, after preparing the thermally conductive composition as described above, a shear force is applied to the thermally conductive composition to produce a pre-formed sheet in which the anisotropic filler material is oriented along the surface direction. Multiple sheets are then stacked to form a laminated block, preferably an oriented molded body. The thermally conductive composition used in the flow orientation method has a high viscosity to withstand shear force when stretched into a sheet shape; specifically, this viscosity is preferably 3 to 500 Pa. s. It can be diluted by adding a suitable solvent to the thermally conductive composition.

[0211] Furthermore, the thermally conductive composition is formed into a sheet by applying shear force to elongate it horizontally, thereby allowing the anisotropic filler material to be oriented along the shear direction. As a means of forming the sheet, the thermally conductive composition is coated onto a substrate film using a coating applicator such as a rod coater or doctor blade, or by extrusion molding or discharge from a nozzle. Then, it is preferable to dry or semi-cur the thermally conductive composition as needed. The thickness of the prepared sheet is preferably about 50 to 5000 μm. In the prepared sheet, the anisotropic filler material is oriented in one direction along the surface direction of the sheet.

[0212] Next, after stacking multiple preparatory sheets in the same orientation direction, the mixture is cured as needed by heating, ultraviolet irradiation, etc., and the preparatory sheets are bonded together by hot pressing to form a stacked block, preferably an oriented molded body.

[0213] [Process (B)]

[0214] In step (B), the oriented molded body obtained in step (A) is cut perpendicularly to the orientation direction of the anisotropic filler material by a slicing or similar means to obtain a sheet-like molded body. Slicing is preferably performed using, for example, a shearing blade or a laser. Sometimes, when the sheet-like molded body is cut by a slicing or similar means, a portion of the anisotropic filler material is exposed from the matrix on each surface that serves as the cut surface.

[0215] The sheet-shaped molded body obtained by slicing in step (B) can be further heated. Heating can then cure the sheet-shaped molded body a second time. In addition, if a coupling agent is mixed in the thermally conductive composition, heating the sheet-shaped molded body can cause some or all of the coupling agent to evaporate.

[0216] The sheet-shaped molded body is heated, for example, at 100–200°C, preferably 120–180°C, for, for example, 30 minutes to 24 hours, preferably 1–6 hours.

[0217] The sheet-shaped molded body obtained through the above process (B) can be used directly as a thermally conductive molded body, but the surface can also be ground, etc. By grinding, the surface condition of the sheet-shaped molded body is improved, which can improve the thermal conductivity.

[0218] It should be noted that the method for obtaining a sheet-like thermally conductive molded body in which the anisotropic filler material is oriented along the thickness direction is not limited to the above; for example, step (B) can be omitted. Specifically, for the magnetic field orientation method, step (B) can be omitted by manufacturing a sheet-like oriented molded body instead of a block-shaped oriented molded body in step (A).

[0219] Furthermore, in cases where a block-shaped thermally conductive molded body is obtained, process (B) can be omitted.

[0220] Furthermore, in the case of obtaining a thermally conductive molded body in which anisotropic filler material is oriented in one direction along the surface direction, part of step (A) and step (B) can be omitted, so that the preparatory sheet obtained in the flow orientation method is a sheet-shaped thermally conductive molded body.

[0221] <Applications of thermally conductive components>

[0222] The thermally conductive molded body of the present invention is preferably used for various electronic components, for example, it is preferably used as a space between a heat-generating element and a heat sink. It is preferable to place the thermally conductive molded body between the heat-generating element and the heat sink to conduct heat emitted by the heat-generating element to the heat sink for heat dissipation. Here, the heat-generating element is not particularly limited, and examples include various electronic components such as CPUs, LEDs, coils, and lithium-ion batteries, as well as wiring with high current flow. Furthermore, examples of heat sinks include heat sinks, heat pumps, and metal casings of electronic devices. In addition, Peltier elements can be used instead of the aforementioned heat sinks, and can be used as peripheral components such as busbars, copper wires, and connectors around the heat-generating element, rather than being directly disposed on it.

[0223] It should be noted that the thermally conductive molded body of the present invention is preferably a thermally conductive molded body with a three-dimensional shape, as described above. By having a three-dimensional shape that corresponds to the shape of the heat-generating body, heat-dissipating body, etc., the fit and conformity to the heat-generating body, heat-dissipating body, etc. can be further improved.

[0224] Example

[0225] The present invention will be further described in detail below by way of examples, but the present invention is not limited by these examples.

[0226] In this embodiment, the evaluation was conducted using the following method.

[0227] [Gel fraction]

[0228] About 2g of the thermally conductive molded body was immersed in 40g of toluene for 1 day. Then, the toluene-insoluble part of the above thermally conductive molded body was taken and dried using a rotary evaporator for 2 hours under a vacuum of -100kPa and a temperature of 50°C. The gel fraction was calculated using the following formula (3).

[0229] Gel fraction = 100 × X / Y (Equation 3)

[0230] In equation (3), X = (Dried mass of toluene-insoluble matter - (Mass of thermally conductive molded body before impregnation × (1 - Ratio of the mass of the organosilicon matrix when the mass of the thermally conductive molded body is set to 1))) Y = (Mass of the thermally conductive molded body before impregnation × Ratio of the mass of the silicone matrix when the mass of the thermally conductive molded body is set to 1) [E Hardness] The E-type hardness of the thermally conductive molded body was determined based on JIS K 6253, a Japanese Industrial Standard. Specifically, the E-type hardness was measured using an E-type hardness tester for the thermally conductive molded bodies produced in each embodiment and comparative example. It should be noted that the measurement was performed using a sample cut from the thermally conductive molded body into a length of 15 mm × width of 15 mm and a thickness of 10 mm.

[0231] [OO hardness]

[0232] The thermally conductive molded bodies produced in the various embodiments and comparative examples were tested for hardness using an OO type hardness tester according to the method of ASTM D2240-05. It should be noted that the tests were performed using specimens cut from the thermally conductive molded bodies to a length of 15 mm × width of 15 mm and a thickness of 10 mm.

[0233] [Flame retardant UL94]

[0234] "Flame retardancy" is certified by American... ライターズ ラボラトリーズ The evaluation was conducted using the flammability test (UL94) established by UnderWriters Laboratories Inc.

[0235] The thermally conductive molded bodies of each experimental and comparative example were cut into test pieces (127 mm in length × 12.7 mm in width × 2 mm in thickness). While held in a fixed clamp with the length of the test piece perpendicular to the flame, the pieces were brought into contact with the flame of a burner for 10 seconds. The burning time of each test piece was recorded after separation from the flame. Furthermore, the duration of the flame after the second contact with the flame (incandescence time) and the presence or absence of dripping material that ignited the absorbent cotton placed below the test piece were recorded. These operations were performed on each test piece in groups of five. Then, based on the judgment criteria shown in Table 1 below, it was determined whether the flame retardancy met the criteria of "V-0" or "V-1". It should be noted that these flame retardancy judgment criteria indicate that "V-0" has higher flame retardancy than "V-1".

[0236] [Table 1]

[0237] [Thermal conductivity]

[0238] Thermal conductivity of thermally conductive molded parts (W / m) K) was determined according to the method of ASTM D5470-06.

[0239] <Components used in the manufacture of thermally conductive molded parts> Organopolysiloxane 1: Organopolysiloxanes with vinyl groups only in the side chains (weight average molecular weight 22500, vinyl concentration 128 μmol / g, viscosity at 23°C 700 mPa) s) Organopolysiloxane 2: Organopolysiloxanes with vinyl groups at both ends (weight-average molecular weight 17700, vinyl group concentration 140 μmol / g). Organopolysiloxane 3: Organopolysiloxanes with vinyl groups at both ends (weight average molecular weight 25400, vinyl concentration 105 μmol / g) Organopolysiloxane 4: Organopolysiloxanes with vinyl groups at both ends (weight-average molecular weight 17100, vinyl group concentration 135 μmol / g). Organopolysiloxane 5: A mixture of organopolysiloxanes with vinyl groups at both ends and organopolysiloxanes with silyl groups at both ends and on the side chains (weight average molecular weight 15700, vinyl concentration 66 μmol / g, silyl group concentration 638 μmol / g). Organopolysiloxane 6: A mixture of organopolysiloxanes with vinyl groups at both ends and organopolysiloxanes with silyl groups at both ends and on the side chains (weight average molecular weight 23300, vinyl concentration 31 μmol / g, silyl group concentration 82 μmol / g). Organopolysiloxane 7: A mixture of organopolysiloxanes with vinyl groups at both ends and organopolysiloxanes with silyl groups at both ends and on the side chains (weight average molecular weight 20,100, vinyl concentration 125 μmol / g, silyl group concentration 103 μmol / g). Organopolysiloxane 8: A mixture of organopolysiloxanes with vinyl groups in the side chains and organopolysiloxanes with hydrosilyl groups (weight average molecular weight 15100, vinyl concentration 59 μmol / g, hydrosilyl concentration 550 μmol / g). Organopolysiloxane 9: Cyclic organopolysiloxanes with silane groups (silane concentration 4415 μmol / g). Organopolysiloxane 10: Organopolysiloxanes with silane groups (weight average molecular weight 20489, silane concentration 1160 μmol / g) *It should be noted that organopolysiloxane 1 and organopolysiloxane 2 contain a catalytic amount of platinum catalyst.

[0240] Dimethyl silicone oil 1: Dimethyl silicone oil (viscosity 300 cs) Dimethyl silicone oil 2: Dimethyl silicone oil (viscosity 110 cs) Dispersant: A compound containing hydroxyl groups, with a number-average molecular weight of 5,000, a hydroxyl equivalent of 2,500, and having the following structure. Reaction delay agent Aluminum hydroxide 1: Aluminum hydroxide (amorphous, D50 = 10 μm) that has undergone dry surface treatment with 7-octenyltrimethoxysilane. Aluminum hydroxide 2: Aluminum hydroxide (amorphous, D50 = 10 μm), a substance that has undergone dry surface treatment with dimethyldimethoxysilane. Aluminum hydroxide 3: Aluminum hydroxide (amorphous, D50 = 10 μm), a substance that has undergone dry surface treatment with n-decyltrimethoxysilane. Aluminum hydroxide 4: Aluminum hydroxide (amorphous, D50 = 54 μm) Aluminum hydroxide 5: Aluminum hydroxide (amorphous, D50 = 54 μm), a substance that has undergone dry surface treatment with dimethyldimethoxysilane. Aluminum hydroxide 6: Aluminum hydroxide (amorphous, D50 = 1.0 μm), a substance surface-treated with stearic acid. Aluminum oxide 1: Aluminum oxide (spherical, D50 = 41 μm) Aluminum oxide 2: Aluminum oxide (spherical, D50 = 41 μm), a substance that has undergone dry surface treatment with 7-octenyltrimethoxysilane. Aluminum oxide 3: Aluminum oxide (spherical, D50 = 2.2 μm), a substance that has undergone dry surface treatment with dimethyldimethoxysilane. Aluminum oxide 4: Aluminum oxide (spherical, D50 = 4.0 μm), a substance that has undergone dry surface treatment with dimethyldimethoxysilane. Aluminum oxide 5: Aluminum oxide (amorphous, D50 = 3.0 μm) Aluminum oxide 6: Aluminum oxide (polyhedral, D50 = 3.0 μm) Aluminum oxide 7: Aluminum oxide (polyhedral, D50 = 0.5 μm) Aluminum oxide 8: Aluminum oxide (polyhedral, D50 = 3.0 μm) after dry treatment with dimethyldimethoxysilane. Aluminum oxide 9: Aluminum oxide (spherical, D50 = 13 μm) Aluminum oxide 10: Aluminum oxide (spherical, D50 = 75 μm) Aluminum oxide 11: Aluminum oxide (disc-shaped, D50 = 4 μm) Coloring pigment: Iron(III) oxide (black pigment) Thixotropic agent: AEROSIL COK84 (Made in Japan by AEROSIL) [Example 1] The components were mixed according to the mixing formula described in Table 2 to obtain a thermally conductive composition. The following evaluation of the moldability of this thermally conductive composition was conducted.

[0241] <Evaluation of formability>

[0242] The use of molds for molding was evaluated. Figure 3 The formability of the thermally conductive molded body 10 with the shape shown. Figure 3 The following figure is a cross-sectional view of the thermally conductive molded body 10. Figure 3 The image above is a top view of a thermally conductive molded body.

[0243] Figure 3 The thermally conductive molded body 10 shown has a shape with 16 trapezoidal protrusions 12 on one side of a plate-shaped molded body 11 arranged in a grid pattern. It should be noted that the thermally conductive molded body has a three-dimensional surface with a surface area of ​​1.46 × A relative to the projected area A in one direction.

[0244] (Evaluation Method)

[0245] Preparation and Figure 3 A mold corresponding to the shape of the thermally conductive molded body 10 was used, and a PET film was adhered to the surface of the upper mold side of the mold. The thermally conductive compositions of each embodiment and comparative example were introduced into the mold and molded at a molding temperature of 120°C and a molding time of 8 minutes. The upper mold with the PET film was lifted and demolded, and the moldability was evaluated based on the number of protrusions 12 remaining in the mold according to the following criteria. It should be noted that case A means the best moldability, and case D means the worst moldability.

[0246] A: 14-16

[0247] B: 11-13

[0248] C: 8-10

[0249] D: Less than 8

[0250] [Examples 2-18, Comparative Examples 1-19]

[0251] The mixture was modified as described in Tables 2-5, and otherwise operated in the same manner as in Example 1. The moldability was evaluated using the thermally conductive composition.

[0252] [Table 2]

[0253] [Table 3]

[0254] [Table 4]

[0255] [Table 5]

[0256] The relationship between the content of the polymer matrix and the gel fraction of the thermally conductive molded articles prepared in Examples 1 to 18 satisfies Equations (1) and (2). As a result, the moldability evaluation of the thermally conductive molded articles in each example is "C" or above, indicating excellent moldability. Furthermore, the thermally conductive molded articles in each example contain a certain amount of thermally conductive filler material, resulting in excellent thermal conductivity.

[0257] Furthermore, Examples 2, 4, 6-8, 12-13, and 15 are thermally conductive molded bodies with low E hardness (below 30). Even with such low hardness, good moldability can be achieved by adjusting the gel fraction and polymer matrix content to a specified range. Additionally, low hardness makes them easy to compress and use, improving workability.

[0258] In contrast, the thermally conductive molded bodies produced in the comparative examples did not satisfy equation (1) or equation (2). As a result, the moldability evaluation was "D", indicating poor moldability.

[0259] Explanation of symbols

[0260] 10 Thermally conductive molded bodies

[0261] 11 Plate shaped body

[0262] 12. A convex portion with a trapezoidal cross-section.

Claims

1. A thermally conductive molded body, characterized in that, It is a thermally conductive molded body containing a polymer matrix and a thermally conductive filler material. The relationship between the gel fraction 'a' of the thermally conductive molded body and the content 'b' of the polymer matrix satisfies both of the following equations (1) and (2), where the unit of 'a' is mass % and the unit of 'b' is volume %. a>1.25×b-4.1 Equation (1) a < 2.87 × b - 33 Equation (2) The method for determining the gel fraction is as follows: (1) Immerse approximately 2g of the thermally conductive molded body in 40g of an organic solvent capable of dissolving the resin components other than the gel component for 1 day. Then, take the organic solvent-insoluble portion of the thermally conductive molded body, dry it, and calculate the gel fraction using the following formula (3). Gel fraction = 100 × X / Y (Equation 3) In equation (3), X = (Dried mass of organic solvent-insoluble matter - (Mass of thermally conductive molded body before impregnation × (1 - Ratio of polymer matrix mass when the mass of thermally conductive molded body is set to 1))) Y = (mass of the thermally conductive molded body before impregnation × ratio of the mass of the polymer matrix when the mass of the thermally conductive molded body is set to 1).

2. A thermally conductive molded body, characterized in that, It is a thermally conductive molded body containing a polymer matrix and a thermally conductive filler material. The relationship between the gel fraction 'a' of the thermally conductive molded body and the content 'b' of the polymer matrix satisfies both of the following equations (1) and (2-2), where the unit of 'a' is mass%, and the unit of 'b' is volume%. a>1.25×b-4.1 Equation (1) a < 4.50 × b - 97 Equation (2-2) The method for determining the gel fraction is as follows: (1) Immerse approximately 2g of the thermally conductive molded body in 40g of an organic solvent capable of dissolving the resin components other than the gel component for 1 day. Then, take the organic solvent-insoluble portion of the thermally conductive molded body, dry it, and calculate the gel fraction using the following formula (3). Gel fraction = 100 × X / Y (Equation 3) In equation (3), X = (Dried mass of organic solvent-insoluble matter - (Mass of thermally conductive molded body before impregnation × (1 - Ratio of polymer matrix mass when the mass of thermally conductive molded body is set to 1))) Y = (mass of the thermally conductive molded body before impregnation × ratio of the mass of the polymer matrix when the mass of the thermally conductive molded body is set to 1).

3. The thermally conductive molded body according to claim 1 or 2, wherein the thermally conductive molded body has a three-dimensional surface having a surface area of ​​1.46 × A or more relative to the projected area A in at least one direction.

4. The thermally conductive molded body according to claim 1 or 2, wherein the content of the polymer matrix is ​​17.5 to 50% by volume.

5. The thermally conductive molded body according to claim 1 or 2, wherein the content of the thermally conductive filler material is 50-82.5% by volume.

6. The thermally conductive molded body according to claim 1 or 2, wherein the polymer matrix is ​​a cured form of an organopolysiloxane.

7. The thermally conductive molded body according to claim 1 or 2, wherein the polymer matrix is ​​a cured body of an addition-reactive organopolysiloxane.

8. The thermally conductive molded article according to claim 1 or 2, wherein the thermally conductive filler material comprises at least one selected from aluminum oxide and aluminum hydroxide.

9. The thermally conductive molded body according to claim 1 or 2, wherein the E hardness is 3 to 90.

10. The thermally conductive molded body according to claim 1 or 2, wherein the thermal conductivity is 1 W / mK or higher.

Citation Information

Patent Citations

  • Heat-conductive holder

    JP2005056837A